Taxonomic revision of the genus Massularia (Rubiaceae, Gardenieae), with a new species from Central Africa - (:unkn) unknown (My University, 2015)
Based on a careful examination of more than 700 herbarium specimens and field investigation, a comprehensive revision of the genus Massularia is given. Massularia stevartiana, a new species from Central African Republic, Cameroon and Gabon is described and illustrated. The novelty is distinguished from M. acuminata, the only other species previously recognized in the genus, by its smaller leaves and flowers. For the two species recognized we provide a morphological description, distribution, habitat, phenology and IUCN conservation status assessment. Distribution maps and a dichotomous key are also provided
Keywords: African Research